ANALISIS YURIDIS PERJANJIAN ANTARA MITRA PENJUAL (MERCHANT) DENGAN PERUSAHAAN PENYEDIA JASA TRANSPORTASI BERBASIS ONLINE (STUDI TERHADAP PERJANJIAN ANTARA APOTIK TERRY FARMA DAN PT SOLUSI TRANSPORTASI INDONESIA (GRAB INDONESIA) - Clara Apulina Ginting; T. Keizerina Devi Azwar -; Jelly Leviza - (jurnal.unprimdn.ac.id, 2021)
High rate of smartphone users makes Medan city has big potential for the development of online-base business especially in service application user, such as online transportation. Grab Indonesia is one of the service provider companies for online-base transportation application. Grab sees promising investment value projection in online-base application service as people in Indonesia are highly active users of social media and e- commerce. The problems in this research are whether the agreement between merchant and Grab Indonesia meet the legal construction as electronic contract refers to valid legislation, how is Grab's responsibilities on product quality and safety sold by merchant, and how is dispute settlement procedures between merchant and Grab Indonesia pursuant to agreement contract. This is a normative juridical research with analytical descriptive design that describes the research object through samples or collected data and makes general conclusion. The data are carried out from primary and secondary data, namely primary, secondary and tertiary law; obtained by library study and guided interview. The result demonstrates that agreement between merchant and Grab meet the legal construction as electronic contract refers to valid legislation. Grab's responsibilities on product quality and safety sold by merchant are fully given to the merchant as stated in the term and condition clauses and in Grab's code of conduct. Non-litigation through arbitrage is prioritized in dispute settlement procedures between merchant and Grab pursuant to agreement contract.